One-Pot Synthesis, Pharmacological Evaluation, Docking Study, and DFT Calculations for Selected Imidazolidine-2,4-Diones - Jawhar, Zanko S.; Ahmad, Hiwa O.; Haydar, Asmaa A.; Abdullah, Halala A.; Mahamad, Sawza A. (Science Journal of University of Zakho, 2018)
The title compounds with different 5-substituted imidazolidine-2,4-dione were synthesized through a solvent-free reaction. Imidazolidine-2,4-dione derivatives are found to be an active pharmacophore for design and development of various bioactive lead compounds.  Positive values of energy obtained for compound 1and 3, while a negative value for compound 2 was calculated by DFT in Gaussian. keto-enol tautomerism was supported by energy values  and indicated the most stable tautomeric form. The biological evaluation has been supported by docking studies using molecular operating environment program to show binding with androgen receptor. Supplementary Materials: https://sjuoz.uoz.edu.krd/suppma
Keywords: imidazolidine-2; 4-dione derivatives; Prostate cancer; computational study; Energy; biological activity